VIP Promotes Recruitment of Tregs to the Uterine–Placental Interface During the Peri-Implantation Period to Sustain a Tolerogenic Microenvironment - Gallino, Lucila; Hauk, Vanesa; Fernández, Laura; Soczewski, Elizabeth; Gori, Soledad; Grasso, Esteban; Calo, Guillermina; Saraco, Nora; Berensztein, Esperanza; Waschek, James A.; Pérez Leirós, Claudia; Ramhorst, Rosanna (Frontiers in Immunology, 2020)
Uterine receptivity and embryo implantation are two main processes that need a finely regulated balance between pro-inflammatory and tolerogenic mediators in order to allow a successful pregnancy. The neuroimmune peptide VIP (vasoactive intestinal peptide) is a key regulator and it is involved in the induction of regulatory T cells (Tregs) which are crucial in both processes. Here, we analyzed the ability of endogenous and exogenous VIP to sustain a tolerogenic microenvironment during the peri-implantation period, particularly focusing on Tregs recruitment. Wild type (WT) and VIP-deficient mice (heterozygous (HT, +/-), knockout (KO, -/-) and FOXP3-knock-in-GFP mice either pregnant or in estrus were used. During the day of estrus we found significant histological differences between the uterus of WT mice vs. VIP deficient mice, with the latter exhibiting undetectable levels of FOXP3 expression, decreased in IL-10 and VEGFc and increased gene expression of the Th17 proinflammatory transcription factor RORγt. To study the implantation window, we mated WT and VIP (+/-) females with WT males and observed altered FOXP3, VEGFc, IL-10 and TGF gene expression at the implantation sites at day 5.5 (d5.5), demonstrating a more inflammatory environment in VIP (+/-) vs. VIP (+/+) females. A similar molecular profile was observed at implantation sites of WTxWT mice treated with VIP antagonist at d3.5. We then examined the ability GFP-sorted CD4+ cells from FOXP3-GFP females to migrate towards conditioned media obtained from d5.5 implantation sites cultured in the absence/presence of VIP or VIP-antagonist. VIP treatment increased CD4+FOXP3+ and decreased CD4+ total cell migration towards implantation sites and VIP-antagonist prevented these effects. Finally, we performed adoptive cell transfer of Tregs (sorted from FOXP3-GFP females) in VIP deficient-mice and we observed that FOXP3-GFP cells were mainly recruited into the uterus/implantation sites compared to all other tested tissues. In addition, after Tregs transfer we found an increase in IL-10 expression and VEGFc in HT females and allowed embryo implantation in KO females. In conclusion, VIP contributes to a local tolerogenic response necessary for successful pregnancy, preventing the development of a hostile uterine microenvironment for implantation by the selective recruitment of Tregs during the peri-implantation period.